Sex ratios, damage and distribution of Myrianthus holstii Engl.: a dioecious afromontane forest tree - Kissa, D.O.; Ssali, F.; Sheil, D. (Cambridge University Press, 2023)
Male and female dioecious tropical trees are subjected to distinct demands that may influence their ecology. An example is Myrianthus holstii Engl. that produces persistent fruit eaten by elephants and other large mammals that frequently damage the trees. Myrianthus holstii populations were assessed with 24 2-km transects, spanning an elevation range of 1435–2495 m in the Bwindi Impenetrable National Park in Uganda. Of 1089 stems ≥ 5 cm diameter 449 were female, 383 were male and the rest were non-fertile. We also noted one apparently monoecious individual. Males produced flowers at smaller sizes than did females (minimum recorded diameters 5.5 cm and 6.8 cm, respectively). Both sexes had similar distributions, favouring moderately closed forest and mid-slope locations. Female trees were more frequently damaged and typically slightly shorter than males at large diameters. Seedling densities were positively associated with the presence of larger female trees. Our results are consistent with a life history where both sexes have similar requirements, but fruiting females experience a greater frequency of severe damage.